Respuesta :

The required polynomial is:[tex]-4x^2-2x+15[/tex]

Step-by-step explanation:

Let P be the polynomial that has to be found

Given

One polynomial = [tex]5x^2-3x-9[/tex]

Sum of both polynomials = [tex]x^2-5x+6[/tex]

So,

[tex](5x^2-3x-9) + P = x^2-5x+6\\P = x^2-5x+6 - (5x^2-3x-9)\\P = x^2-5x+6-5x^2+3x+9\\P = x^2-5x^2-5x+3x+6+9\\P = -4x^2-2x+15[/tex]

Hence,

The required polynomial is:[tex]-4x^2-2x+15[/tex]

Keywords: Polynomials, expressions

Learn more about polynomials at:

  • brainly.com/question/1704778
  • brainly.com/question/1695461

#LearnwithBrainly